Cystic fibrosis management in pediatric population—from clinical features to personalized therapy - Azoicai, Alice Nicoleta; Lupu, Ancuta; Trandafir, Laura Mihaela; Alexoae, Monica Mihaela; Alecsa, Mirabela; Starcea, Iuliana Magdalena; Cuciureanu, Magdalena; Knieling, Anton; Salaru, Delia Lidia; Hanganu, Elena; Mocanu, Adriana; Lupu, Vasile Valeriu; et al. (Frontiers in Pediatrics, 2024)
Cystic fibrosis (CF) is an autosomal recessive disease caused by mutations of the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR). In 1949, it's been identified as a monogenic disease and was thought to primarily affect individuals of Northern European descent. It was the most prevalent autosomal recessive disease that shortens life. With the availability of multiple testing methodologies nowadays, there is a chance to create novel and enhanced treatment options. Even in the absence of a high sweat chloride test (SCT) result, the discovery of two causal mutations is diagnostic for cystic fibrosis (CF). For a CF diagnosis, however, at least two positive E sweat chloride tests are still required. In order to achieve early and active intervention to manage cystic fibrosis (CF) and its comorbidities, treatment regimens for pediatric patients should be evaluated, improved, and closely monitored. New developments in the treatment of cystic fibrosis (CF) have led to the development of medications derived from molecules that target the pathogenetic pathway of the illness. These options are very efficient and allow pediatric patients to receive individualized care. However, in order to better direct patient care and enhance patient outcomes, it is crucial to research uncommon CF mutations, which can provide crucial information about the prognosis of the disease and the relationships between genotype and phenotype. To ensure the success of creating novel, safer, and more efficient treatment approaches, a deeper understanding of the pathogeny of the illness is required. In the age of customized medicine, genetic research will be essential to improving patient care and quality of life for those with uncommon mutations.